Postdural Puncture Headache - Ghaleb, Ahmed (Hindawi Publishing Corporation, 2010)
Postdural puncture headache (PDPH) has been a problem for patients, following dural puncture, since August Bier reported the first case in 1898. His paper discussed the pathophysiology of low-pressure headache resulting from leakage of cerebrospinal fluid (CSF) from the subarachnoid to the epidural space. Clinical and laboratory research over the last 30 years has shown that use of small-gauge needles, particularly of the pencil-point design, is associated with a lower risk of PDPH than traditional cutting point needle tips (Quincke-point needle). A careful history can rule out other causes of headache. A postural component of headache is the sine qua non of PDPH. In high-risk patients , for example, age < 50 years, postpartum, large-gauge needle puncture, epidural blood patch should be performed within 24–48 h of dural puncture. The optimum volume of blood has been shown to be 12–20 mL for adult patients. Complications of AEBP are rare.